Combining combinatorial chemistry and affinity chromatography: highly selective inhibitors of human betaine: homocysteine S-methyltransferase - Collinsová, Michaela; Castro, Carmen; Garrow, Timothy A; Yiotakis, Athanasios; Dive, Vincent; Jirácek, Jirí (Chemistry & biology, 2003)
A new method to find novel protein targets for ligands of interest is proposed. The principle of this approach is based on affinity chromatography and combinatorial chemistry. The proteins within a crude rat liver homogenate were allowed to interact with a combinatorial library of phosphinic pseudopeptides immobilized on affinity columns. Betaine: homocysteine S-methyltransferase (BHMT) was one of the proteins that was retained and subsequently eluted from these supports. The phosphinic pseudopeptides, which served as immobilized ligands for the isolation of rat BHMT, were then tested for their ability to inhibit human recombinant BHMT in solution. The most potent inhibitor also behaved as a selective ligand for the affinity purification of BHMT from a complex media. Further optimization uncovered Val-Phe-psi[PO(2-)-CH(2)]-Leu-His-NH(2) as a potent BHMT inhibitor that has an IC(50) of about 1 microM.
Keywords: Electrophoresis, Polyacrylamide Gel; játra; Ligands; techniky in vitro; Humans; ligandy; elektroforéza v polyakrylamidovém gelu; Methyltransferases; Enoyl-CoA Hydratase; Molecular Sequence Data; Betaine-Homocysteine S-Methyltransferase; molekulární sekvence - údaje; Blotting, Western; krysa rodu Rattus; lidé; Recombinant Proteins; chromatografie afinitní; zvířata; peptidová knihovna; peptidy; potkani Wistar; Glutathione Transferase; Chromatography, Affinity; Peptides; kyseliny fosfinové; techniky kombinatorické chemie; Amino Acid Sequence; rekombinantní proteiny; Liver; enoyl-CoA-hydratasa; Rats, Wistar; Male; Combinatorial Chemistry Techniques; In Vitro Techniques; inhibitory enzymů; Rats; Peptide Library; Animals; betain-homocystein-S-methyltransferasa; western blotting; mužské pohlaví; glutathiontransferasa; methyltransferasy; Enzyme Inhibitors; Phosphinic Acids; sekvence aminokyselin